Qualidade de vida do cuidador familiar e dependência do paciente com alzheimer (2010)
The purpose of the study was to establish the relation between the quality of life of the family caregiver and the level of dependence of the patient with Alzheimer. It is a co-relational descriptive, cross-sectional study, with a quantitative approach having participation of 192 family caregivers of patients with Alzheimer; they are part of the Cuidado a Cuidadores® (Care for Caregivers) program of the Nursing Faculty of Universidad Nacional de Colombia, the Fundación Acción Familiar Alzheimer Colombia (Alzheimer Colombia Family Action Foundation) and the Asociación Nacional de Alzheimer (Colombian Alzheimer Association). Betty Ferrell´s “Quality of life, the family version” instrument (QOL) was applied. She defines quality of life from the physical, psychological, social and spiritual dimensions. Barthel Index (BI), which measures the patient´s level of functional dependence, was also applied. Caregivers’ general quality of life obtained an average score. Physical and spiritual welfare showed a positive trend, while the psychological and social wellbeing of this population group showed a negative trend with an alteration risk for the future. The Alzheimer patient’s functional dependence level was found from total to severe dependence, with a great commitment in personal care and hygiene activities. The study did not show any statistical correlation between quality of life and the level of dependence of the patient with Alzheimer.